Filogenia de Tibraca limbativentris Stal 1860 (Hemiptera: pentatomidae) utilizando marcador mitocondrial COI - Santos, Luciana Lins Oliveira (2017)
The stink bug Tibraca limbativentris is a phytophagous insect of the family Pentatomidae that causes many damages in rice fields. Its distribution in Maranhão occurs in upland or rainfed crops, but it is also possible to find it in humid floodplains. Phylogenetic studies of species allow us to estimate the evolutionary relationships of different groups. The highest applicability is associated to the correct systematic classification and grouping of the species, considering morphological, behavioral and genetic characters, which may imply in pest management systems. The search for similarity between individuals indicates the paths traveled by the species in the evolutionary course. The phylogenetic systematics is a tool based on several methods, but the sequencing of regions of the gene strengthens the similarity relations. These relationships can be estimated by the divergence and indices of genetic diversity and represented by phylogenetic trees. In this work, the objective of this study was to infer and understand the phylogenetic relationships of T. limbativentris from different orchards in different locations of Maranhão (Arari, Viana, São Mateus, Pedreiras, Nina Rodrigues, Zé Doca and Caxias) and other neotropical species of Pentatomideos, using the mitochondrial DNA marker COX1. The analyzes were done with only 27 Tibraca sequences, from which nine haplotypes were generated. The genetic distances for T. limbativentris were low with a mean of 0.41% and values above 14% among the external group. The arrangement of the phylogenetic tree confirmed the results of divergence presenting a single clade for the populations of Tibraca. Neutrality tests indicated that the population group of the species has undergone recent population expansion and that the species does not follow the constant size model.